2017
DOI: 10.1371/journal.pone.0172349
|View full text |Cite
|
Sign up to set email alerts
|

One species or four? Yes!...and, no. Or, arbitrary assignment of lineages to species obscures the diversification processes of Neotropical fishes

Abstract: Species are fundamental units in many biological disciplines, but there is continuing disagreement as to what species are, how to define them, and even whether the concept is useful. While some of this debate can be attributed to inadequate data and insufficient statistical frameworks in alpha taxonomy, an equal part results from the ambiguity over what species are expected to represent by the many who use them. Here, mtDNA data, microsatellite data, and sequence data from 17 nuclear loci are used in an integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 105 publications
0
29
0
Order By: Relevance
“…We make this assertion with caution, 466 however, because detailed phylogeographic studies of Neotropical cichlids have shown 467 that at least some taxa may be affected by these problems, particularly at more recent 468 levels of divergence (e.g. Willis et al 2013Willis et al , 2017. Even more germane to our study, the 469 persistence of unresolved or poorly supported "deep" relationships within a few clades of 470…”
Section: Discussion 433mentioning
confidence: 85%
“…We make this assertion with caution, 466 however, because detailed phylogeographic studies of Neotropical cichlids have shown 467 that at least some taxa may be affected by these problems, particularly at more recent 468 levels of divergence (e.g. Willis et al 2013Willis et al , 2017. Even more germane to our study, the 469 persistence of unresolved or poorly supported "deep" relationships within a few clades of 470…”
Section: Discussion 433mentioning
confidence: 85%
“…We therefore hypothesised that the aforementioned extreme life history diversity of isopods might cause pronounced compositional heterogeneity/heterotachy in their mitogenomes, and interfere with the reconstruction of the Isopoda phylogeny. Although limitations of mitochondrial (and molecular in general) data for inferring phylogenies have been widely discussed (Ballard & Whitlock, 2004; Edwards, Potter, Schmitt, Bragg, & Moritz, 2016; Grechko, 2013; Hassanin, Léger, & Deutsch, 2005; Rubinoff, Holland, & Savolainen, 2005; Talavera et al, 2011; Willis, 2017), a review of the existing literature reveals that most previous studies of evolutionary history of Isopoda ignored those limitations, or attempted to ameliorate them by using such strategies combined datasets (mtDNA, nuclear DNA, morphology) (Luana S.F. Lins et al, 2017; G D F Wilson, 2009), amino acid sequences (Kilpert et al, 2012; Luana S.F.…”
Section: Introductionmentioning
confidence: 99%
“…If true, this would deal a death blow to the species category as a well-founded currency in comparative biology. Studies highlighting this worrying possibility such as those by Riddle andHafner (1999), Faurby et al (2016) or Willis (2017) should be a wake-up call and an alarm signal that we draw the wrong conclusions from alpha taxonomy. Both and Zachos et al (2013) (see also Zachos 2018aZachos , 2019 worry that the arbitrary part in the aforementioned alpha taxonomy equation negatively impacts conservation biology because decisions are based too much on the executivedecision part of species and too little on the scientific data that gave rise to that decision.…”
Section: Taxonomy's Twofold Nature and Its Inherent Limitationsmentioning
confidence: 98%
“…), the final choice is an individual preference. We are not alone in sharing our concern about this twofold nature of taxonomy (see, for example, Heywood 1998, Mishler 1999, Hendry et al 2000, Willis 2017, Mishler and Wilkins 2018 but consider it an inescapable consequence of the fundamental object of taxonomic research: delineating discrete entities out of an evolutionary continuum that inevitably means boundaries are fuzzy. This is an inherent limitation of taxonomy of which users of taxonomy should be more aware.…”
Section: Taxonomy's Twofold Nature and Its Inherent Limitationsmentioning
confidence: 99%